The Moon among Stars and The Throne in the Forest : Image and formula in the 'Nibelungenlied' and the 'Ramayana' - Dalzell, Pauline (Trinity College (Dublin, Ireland). Department of Germanic Studies, 2002)
The point of reference in earlier comparative studies of epic featuring either the medieval German Nibelungenlied or the ancient Indian Ramayana as one component of the comparison has been narrative content, narrative technique and/or structure. To my knowledge this is the first study not only to combine the two poems in question but also to make a text-based examination of imagery rather than narratology the basis of a comparative study of epic. The absence of an intertextual link between the two works makes the analogies more remarkable, but the methodology used takes note both of homologies and of disparities, since it is difference as much as similarity which broadens knowledge about the nature of the epic genre. Having outlined the ongoing debate on oral and written narrative poetry, especially with reference to formulaic expression and the opposing theories of 'composition in performance' and 'verbatim memorisation', this study proceeds to discuss the internal, and, where possible, external evidence indicating the oral composition and aural reception of the Nibelungenlied and the Ramayana. Then follows a general consideration of the poetic image in concept and in practice, drawing in part on prescriptive material found in each tradition and making frequent use of illustrative examples from the Nibelungenlied and the Ramayana. It establishes definitions of the terms which will be used to distinguish between the two types of imagery to be explored in this thesis, namely a) the poetic image as figure of speech and b) the poetic image as symbol. Building on these definitions, the study proceeds to textual examination of examples of stock simile common to the texts and to suggest possible functions of formulaic imagery in the compositional dynamics of the epics. A comparative analysis of symbolic images of sovereignty follows. The imagery centres around the formulaic diametrically opposite symbols of the City, the centre of socio-political structures, and the mythical Forest (the location of the metaphorical throne of the thesis title) which is at the same time both the negation and the validation of these structures, and thirdly the City which lies within the Forest and contains elements of both City and Forest. This contextual investigation leads to an assessment of the function of these three types of symbols in portraying the kingship of Siegfried and Rama: what these symbols tell us specifically about the similarities and differences in their nature and rule.
Keywords: Germanic Studies, Ph.D.; Ph.D. Trinity College Dublin